The Unreal Estate Guide to Detroit - Herscher, Andrew, 1961- (Book collections on Project MUSE., 2012)
The Detroit Unreal Estate Agency was founded in 2008 as an open-access platform for research on urban crisis, using Detroit as a focal point. Against the apprehension of Detroit as a problem that needs to be solved, the Agency has regarded Detroit as a site where new ways of imagining, inhabiting and constructing the contemporary city are being invented, tested and advanced.